Water Hyacinth (Eceng Gondok) As Fibre Reinforcement Composite for Prosthetics Socket. (August 2019) - Widhata, D; Ismail, R; Sulardjaka,
Abstract: Based on the study of water hyacinth fibres, the results of tensile tests and compressive flexural tests for water hyacinth fibre composites laminated with methyl methacrylate resin as reinforcing materials for the manufacture of trans femoral socket prosthesis, showed there is no significant difference in strength and flexibility between water hyacinth fibres and nylon glass fibre which is more often using in orthopaedics technology. Objectives: This study aims to engineer water hyacinth fibre as reinforcing materials for fabricating trans femoral sockets and perform the structural testing. Study Design: Experimental, bench research. Result: The availability and renewable natural fibres has the potential to reduce hazards for those involved in manufacturing the artificial limb sockets, without reducing and compromising the strength of sockets and benefiting for the users. Wall thickness, fibre direction and fibre-matrix resin lamination played a significant role in socket strength. Conclusions: From this limited study we conclude that the resin and water hyacinth fibre composite socket has the potential to replace the standard layup. Further mechanical and biocompatibility testing as well as a full economic analysis is required. Thus, the use of composites with water hyacinth fibres has the potential to be further developed as an alternative material for socket prosthesis in Indonesia.